Epidemiology and control of powdery mildew (Oidium anacardii Noack) on cashew (Anacardium occidentale L.) in Mozambique - Korsten, Lise (University of Pretoria, 2013)
Dissertation (MSc(Plant Pathology))--University of Pretoria, 2003.